2021
DOI: 10.21608/svu.2021.64991.1111
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of Pseudomonas species isolated from Fish Marketed in Sohag Governorate, Egypt

Abstract: The aims of this study were isolation and characterization of Pseudomonas spp. from fish meat collected from Sohag governorate, Egypt. A total 120 fish samples including frozen mackerel, frozen saurus, chilled Mugil cephalus and chilled Tilapia nilotica (30 of each) were collected from different shops and supermarkets in Sohag governorate. Pseudomonas spp. were isolated from 65% of the examined samples. The obtained data revealed that the highest count of Pseudomonas was in chilled Tilapia nilotica. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
4
4
0
Order By: Relevance
“…The study appeared that oprL genes were present in 97.5% of P. aeruginosa isolates that produce positive PCR amplicons products at 504 bp. These findings in consent with the findings each of Abd-El-Maogoud et al (9), Algammal et al (18), and Mehri et al (24) who showed that all tested strains 100% harbored this gene. The oprL gene contributes significantly to the resistance of this bacterium to antibiotics and disinfectants, as it directly affects the efflux systems, which in turn affects the permeability of the cell membrane to antibiotics (3), as well as oprL could be a reliable factor for diagnosis of P. aeruginosa in environmental and clinical isolates (20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study appeared that oprL genes were present in 97.5% of P. aeruginosa isolates that produce positive PCR amplicons products at 504 bp. These findings in consent with the findings each of Abd-El-Maogoud et al (9), Algammal et al (18), and Mehri et al (24) who showed that all tested strains 100% harbored this gene. The oprL gene contributes significantly to the resistance of this bacterium to antibiotics and disinfectants, as it directly affects the efflux systems, which in turn affects the permeability of the cell membrane to antibiotics (3), as well as oprL could be a reliable factor for diagnosis of P. aeruginosa in environmental and clinical isolates (20).…”
Section: Discussionsupporting
confidence: 92%
“…The virulence mechanisms in P. aeruginosa varies depending on the infection environment (3). Many infections are caused by P. aeruginosa as a result of high resistance against antibiotics (8), which is due to the synergistic relationship between the effect of the low permeability of the cellular outer membrane and the existence of multidrug efflux pump in turn directly excludes antibiotics out of the cell (9). Lipoproteins play an important role in many processes necessary for bacterium cells, as adapting the bacteria to the environment and in bacterial infections outer membrane protein of this bacterium which contributes to resisting the antibiotics and disinfectant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benie et al [ 23 ] isolated 153 multidrug-resistant strains of Pseudomonas aeruginosa from beef (93), fresh fish (36), and smoked fish (24) [ 19 ]. Abd-El-Maogoud et al [ 24 ] isolated P. aeruginosa from 65% of frozen mackerel (33%), frozen Sarus (30%), and tilapia samples (23%) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, P. aeruginosa strains isolated in Egypt showed multidrug resistance (MDR) to amoxicillin, cefotaxime, tetracycline, and gentamicin [ 20 ]. Carol et al [ 26 ] observed that P. aeruginosa had high resistance to amoxicillin, moderate resistance to ampicillin, ceftazidime, nitrofurantoin, and gentamicin sensitivity tobramycin, cefotaxime, methylene, ciprofloxacin, and amikacin [ 24 ]. Benie et al [ 21 ] examined the prevalence of P. aeruginosa in beef, fresh fish, and smoked fish.…”
Section: Resultsmentioning
confidence: 99%